Genetic Polymorphism of Cytochrome P450 4F2, Vitamin E Level and Histological Response in Adults and Children with Nonalcoholic Fatty Liver Disease Who Participated in PIVENS and TONIC Clinical Trials - Athinarayanan, Shaminie; Wei, Rongrong; Zhang, Min; Bai, Shaochun; Traber, Maret G.; Yates, Katherine; Cummings, Oscar W.; Molleston, Jean; Liu, Wanqing; Chalasani, Naga (PLOS ONE, 2014)
Vitamin E improved liver histology in children and adults with NAFLD who participated in TONIC and PIVENS clinical trials, but with significant inter-individual variability in its efficacy. Cytochrome P450 4F2 (CYP4F2) is the major enzyme metabolizing Vit E, with two common genetic variants (V433M, rs2108622 and W12G, rs3093105) found to alter its activity. We investigated the relationship between CYP4F2 genotypes, α-tocopherol levels and histological improvement in these two trials. V433M and W12G variants were genotyped in TONIC (n = 155) and PIVENS (n = 213) DNA samples. The relationships between CYP4F2 genotypes, plasma α-tocopherol levels at baseline and weeks 48 (w48) and 96 (w96) and histological end points (overall improvement in liver histology and resolution of NASH) were investigated. As a result, the V433M genotype was significantly associated with baseline plasma α-tocopherol in the TONIC trial (p = 0.004), but not in PIVENS. Among those receiving Vit E treatment, CYP4F2 V433M genotype was associated with significantly decreased plasma α-tocopherol levels at w48 (p = 0.003 for PIVENS and p = 0.026 for TONIC) but not at w96. The w96 α-tocopherol level was significantly associated with resolution of NASH (p = 0.006) and overall histology improvement (p = 0.021)in the PIVENS, but not in the TONIC trial. There was no significant association between CYP4F2 genotypes and histological end points in either trial. Our study suggested the a moderate role of CYP4F2 polymorphisms in affecting the pharmacokinetics of Vit E as a therapeutic agent. In addition, there may be age-dependent relationship between CYP4F2 genetic variability and Vit E pharmacokinetics in NAFLD.